The Impact of Product Packaging and Packaging Design on Consumer Behavior in North Sulawesi (Study Case on Wardah Cosmetics) - Lingkan J Kalangi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
emergence of the Covid-19 outbreak which has further complicated the development of products that are being marketed. Companies are required to continue to try to maintain customer trust and loyalty in order to continue to see their products. That's why looking at the cosmetics market today companies are competing to make products more innovative and of high quality both in terms of packaging and design, as well as for the product itself so that it can influence consumer behavior in buying products that are marketed. The purpose of this study is to analyze the influence of product packaging and product design from Wardah Cosmetics to influence consumer purchasing behavior.Â  The type of method carried out is quantitative research methods. The sampling method is carried out by distributing questionnaires to Wardah Cosmetics consumers. The results obtained from this study are that product packaging and packaging design have a significant effect on the purchasing behavior of consumers of Wardah products.Â Keyword: Product Packaging, Packaging Design, Consumer Buying Behavior